Secondary flow in bifurcations – Important effects of curvature, bifurcation angle and stents. (2nd December 2021) - Shen, C.; Gharleghi, R.; Li, D.D.; Stevens, M.; Dokos, S.; Beier, S.
Abstract: Coronary bifurcations have complex flow patterns including secondary flow zones and helical flow, which directly affect pathophysiological mechanisms such as the development of atherosclerosis. The objective of this study was to generate insights into the effects of curvature, bifurcation angle and the presence of stents on flow patterns and resulting haemodynamics in coronary left main bifurcations. The blood flow and associated metrics were modelled in both idealised and patient-specific bifurcations with varying curvature and bifurcation angles with and without stents, resulting in a total of 128 geometries considered. The results showed that larger curvature of bifurcating vessels has a significant influence on secondary flow, especially with distance to the bifurcation region, causing a skew, spin and asymmetry of Dean vortices, an increase in helical flow intensity with symmetry loss, and a decrease in adversely low time-average wall shear stress (TAWSS). Generally, asymmetric flow patterns coincided with adversely low TAWSS regions. In identical stented geometries, the presence of the stents induced local recirculation immediately adjacent to the stent struts, thus generating adversely low TAWSS in these areas, with some effect on the overall secondary flow. Overall, the effect of stents outweighed the effect of curvature and BA. This new knowledge contributes to a better understanding of the joint effects of curvature, bifurcation angle, and stents on flow patterns and haemodynamics in coronary bifurcations.